Correlates of self worth and body size dissatisfaction among obese Latino youth - Mirza, Nazrat M (2011)
The current study examined self-worth and body size dissatisfaction, and their association with maternal acculturation among obese Latino youth enrolled in a community-based obesity intervention program. Upon entry to the program, a sample of 113 participants reported global self-worth comparable to general population norms, but lower athletic competence and perception of physical appearance. Interestingly, body size dissatisfaction was more prevalent among younger respondents. Youth body size dissatisfaction was associated with less acculturated mothers and higher maternal dissatisfaction with their child's body size. By contrast, although global self-worth was significantly related to body dissatisfaction, it was not influenced by mothers’ acculturation or dissatisfaction with their own or their child’s body size. Obesity intervention programs targeted to Latino youth need to address self-worth concerns among the youth as well as addressing maternal dissatisfaction with their children’s body size.